2015
DOI: 10.1016/j.jcin.2015.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Health Status After Transcatheter or Surgical Aortic Valve Replacement in Patients With Severe Aortic Stenosis at Increased Surgical Risk

Abstract: Background In patients at increased surgical risk, TAVR with a self-expanding bioprosthesis is associated with improved 1-year survival compared with AVR. However, elderly patients may be just as concerned with quality of life improvement as with prolonged survival as a goal of treatment. Objectives To compare the health status outcomes for patients treated with either self-expanding transcatheter aortic valve replacement (TAVR) or surgical aortic valve replacement (AVR). Methods Between 2011 and 2012, 795… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
1
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 18 publications
1
61
1
3
Order By: Relevance
“…2,3,6,7 Nonetheless, there are several subtle differences in outcomes between the pivotal trials and the TVT registry. For example, the changes in the KCCQ-OS at 30 days and 1 year in TVT of 27 and 32 points, respectively, are ~5–10 points greater than those seen in the PARTNER A and B and CoreValve clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,6,7 Nonetheless, there are several subtle differences in outcomes between the pivotal trials and the TVT registry. For example, the changes in the KCCQ-OS at 30 days and 1 year in TVT of 27 and 32 points, respectively, are ~5–10 points greater than those seen in the PARTNER A and B and CoreValve clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pivotal trials demonstrated both survival and quality of life (QOL) benefits of TAVR within select cohorts of patients and hospital centers, 17 it is critical to understand how this novel technology performs as it moves beyond experienced centers and operators and outside of the strict inclusion and exclusion criteria of the clinical trials. In order to understand these outcomes more fully, the Society of Thoracic Surgeons (STS) and the American College of Cardiology (ACC) developed the STS/ACC Transcatheter Valve Therapy (TVT) Registry.…”
mentioning
confidence: 99%
“…Nonetheless, some patients do not improve functionally or live long following TAVR, with approximately 1 in 4 patients treated with TAVR dying within 1 year (4). Moreover, despite substantial improvement in QOL for many patients, a sizeable minority continues to experience significant heart failure symptoms, with associated functional limitation and poor QOL (59). …”
mentioning
confidence: 99%
“…[1][2][3][4][5] In fact, recent analyses from 2 separate randomized controlled trials have reported that healthrelated quality of life improves earlier and faster among highrisk patients assigned to transfemoral TAVR, as compared with surgical aortic valve replacement. 6,7 Nevertheless, it is becoming increasingly clear that not all patients assigned to TAVR benefit from the procedure. For example, in the CoreValve US Pivotal trial, extreme risk cohort (mean Society of Thoracic Surgeons [STS] score 10.4±5.6%), 39% of patients were deemed to have had a poor outcome after TAVR (22% death, 16% poor quality of life, and 1.4% quality of life decline).…”
mentioning
confidence: 99%
“…Therefore, health-related quality of life may serve as a useful surrogate marker for the combined effect of a patient's age, AS severity, comorbidities, and frailty parameters. Although there have been several studies quantifying improvements in health-related quality of life as compared with baseline following TAVR, [4][5][6][7][8] it remains unclear whether the status of baseline health-related quality of life per se may serve as a useful parameter for further risk stratification of patients before the procedure.…”
mentioning
confidence: 99%